2020
DOI: 10.1242/jeb.216499
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for a role of dopamine on avian personality traits

Abstract: There is increasing interest in the genetic and physiological bases of behavioural differences among individuals, namely animal personality. One particular dopamine (DA) receptor gene (the dopamine receptor D4 gene) has been used as candidate gene to explain personality differences, but with mixed results. Here, we used an alternative approach, exogenously manipulating the dopaminergic system and testing for effects on personality assays in a social bird species, the common waxbill (Estrilda astrild). We treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
0
9
1
Order By: Relevance
“…Although genes with the highest fold change do not necessarily have the highest biological significance, these receptors are strong candidates for future work. Dopamine receptor 2 specifically has already been linked to personality traits such as boldness and novelty seeking in other species [88][89][90]. Surprisingly, neophobic birds in our study showed no evidence for differential expression of the dopamine receptor 4 (DRD4) gene in any of the four brain regions we examined.…”
Section: Discussioncontrasting
confidence: 47%
“…Although genes with the highest fold change do not necessarily have the highest biological significance, these receptors are strong candidates for future work. Dopamine receptor 2 specifically has already been linked to personality traits such as boldness and novelty seeking in other species [88][89][90]. Surprisingly, neophobic birds in our study showed no evidence for differential expression of the dopamine receptor 4 (DRD4) gene in any of the four brain regions we examined.…”
Section: Discussioncontrasting
confidence: 47%
“…Lack of dopamine results in depletion of the nervous system, and its increased level causes bipolar disorders [4,27]. It has been shown that in people with the long form of the DRD4 gene (the number of repeats is six or more), the affinity of dopamine for the receptor is reduced and the number of receptors is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…These brain structures play a vital part in the implementation of psychomotor, cognitive, neuroendocrine functions [3]. Relationship between 'novelty seeking' and dopamine system has been found: an association of temperament with genetic polymorphism encoding the fourth type dopamine receptor (DRD4) was established [4].…”
Section: Introductionmentioning
confidence: 99%
“…The second is that individual birds even of the same species may react very differently to the world and will do so according to individual personality traits [ 81 , 82 ]. There is now plenty of evidence that personality or temperament has a good deal to do with a bird’s reproductive success and overall health [ 60 , 61 , 83 , 84 ]. They can suffer ‘mental’ health issues of varying degrees of severity—the worst of which, in cockatoos (family Cacatuidae), are stages of catatonic immobility and swaying while not attending to any external stimuli [ 27 ].…”
Section: Birds In Captive Environments: Identifying or Avoiding Behavioral Problemsmentioning
confidence: 99%